2019
DOI: 10.1177/0300060519834447
|View full text |Cite
|
Sign up to set email alerts
|

Renal function, complications, and outcomes of a reduction in tumor size after transarterial embolization for renal angiomyolipomas: a meta-analysis

Abstract: Objective The present study aimed to evaluate renal function, complications, and changes in tumor size after transarterial embolization for patients with renal angiomyolipomas. Methods We performed a meta-analysis of transarterial embolization in patients with renal angiomyolipomas from January 1994 to April 2018. Endpoints of interest were the estimated glomerular filtration rate, serum creatinine levels, blood urea nitrogen levels, complications, and reduction of tumors. Results A total of 30 studies compris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 55 publications
(99 reference statements)
3
22
0
Order By: Relevance
“…Nonsteroidal anti-inflammatory agents or corticosteroids are effective against these symptoms. In a meta-analysis of 30 studies, PES occurred in 54% of cases, in keeping with our data [ 23 ]. Lower frequencies of 6% to 12.5% were observed in studies that involved routine nonsteroidal anti-inflammatory drug therapy [ 7 , 39 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Nonsteroidal anti-inflammatory agents or corticosteroids are effective against these symptoms. In a meta-analysis of 30 studies, PES occurred in 54% of cases, in keeping with our data [ 23 ]. Lower frequencies of 6% to 12.5% were observed in studies that involved routine nonsteroidal anti-inflammatory drug therapy [ 7 , 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…SAE is a well-established treatment option for patients with rAMLs that cause bleeding or are at high risk for bleeding. This minimally invasive technique preserves kidney function and has a low complication rate [ 10 , 22 , 23 ]. However, the optimal embolization material is unclear, as most studies did not provide data on individual agents and/or pooled patients treated with different agents [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the different proportions of blood vessels, smooth muscles, and fat in different tumors, the degree of tumor shrinkage after SAE treatment also differs; in particular, tumors with high fat content do not show significantly reduced volume (19,20). We therefore decided to combine SAE therapy with RFA because our experience and published data (1,(17)(18)(19)(20) suggest that treatment with SAE alone may not result in rapid tumor shrinkage. We did not apply SAE and RFA sequentially, but used both immediately, as sequential therapy may risk the disappearance of lipiodol or the granular embolic agent, the formation of newly-developed collateral vessels, and the recanalization of the embolized blood vessels.…”
Section: A B C Dmentioning
confidence: 99%
“…In 2015, Murray et al performed a systematic review of trans-arterial embolization for RAMLs and reported a high technical success of 93.3% and a mean reduction in tumor size of 3.4 cm [15]. Lin et al reported SAE of RAMLs affected renal function preservation, and had a low complication rate, with a mean reduction in the size of 2.09 cm after meta-analyzing 30 studies [16]. Sun et al conducted a real-world study to compare embolization and nephrectomy for renal RAMLs associated with TSC, and embolization was effective, with a reduction in gross hematuria (− 27.7%), retroperitoneal hemorrhage (− 8.4%), and abdominal mass (− 6.9%) [17].…”
Section: Discussionmentioning
confidence: 99%